Implementasi Projek Emanhot (Edukasi Menanam Hortikultura) untuk Menumbuhkan Kepedulian Lingkungan pada Siswa Kelas 1 SD Negeri 1 Winduhaji - Eva Putri Puspitasari; Fanisa Salsabilla; Farid Al Pajri (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The EMANHOT programme (Education in Horticultural Planting) aims to instil environmental awareness in grade 1 students of Winduhaji State Elementary School 1 through a contextual and project-based learning approach. The method used is descriptive qualitative, with the research subjects being 45 students from classes 1A and 1B. Activities range from initial education about the benefits of plants, direct planting practices, to monitoring and reflection. The results show a significant increase in student involvement in caring for the plants, as well as the development of character values such as responsibility, cooperation, and environmental concern. Students became more active in watering the plants, naming their plants, and engaging their parents in planting at home. This project also creates an educational green space at school and has the potential to be integrated with local content as well as the Strengthening the Profile of Pancasila Students Project (P5).